Analysis of High School Students’ Chemical Mental Models Based on Three Levels of Chemical Representation: A Literature Study - I Wayan Suja; I Gusti Lanang Wiratma; Ida Bagus Nyoman Sudria; Qonita Awliya Hanif (Postgraduate, University of Mataram, 2026)
This study aimed to determine the profile of the chemical mental models of high school students and to describe and explain the factors that caused the formation of alternative mental models in students' minds. This research was classified as a document analysis involving 15 theses in the Chemistry Education Study Program, Universitas Pendidikan Ganesha (Undiksha) as research subjects and students’ chemical mental models as the research object. Data collection was done by using a checklist. The data collected underwent descriptive analysis. The results of the study showed that students' chemical mental models included Scientifically Correct as much as 0–28.65%; Partially Correct as much as 23.03%–90.58%; specific misconceptions reaching 0.48%–58.53%; and No Response as much as 0–49.07%. Factors causing the formation of alternative mental models in students' minds include a low understanding at the submicroscopic level, overgeneralization, ignorance of the meaning of chemical symbols, a lack of information related to the complexity of the problem at hand, a lack of understanding of prerequisite concepts, analogy errors, and errors in the learning materials. In general, alternative mental models are arise when students do not understand the submicroscopic structure underlying the properties of substances.